Potential of coastal headlands for tidal energy extraction and the resulting environmental effects along Negeri Sembilan coastlines: A numerical simulation study - Goh, H.-B. (Elsevier Ltd, 2020)
Strong tidal currents can normally be observed around coastal headlands due to their geometrical effects. The effects of the physical characteristics of headlands, such as the size and location, as well as the channel width, on energy production have not been well explored to date. This study has been set to measure the energy production potential at four different sizes of coastal headlands along Negeri Sembilan coastlines, and to gauge the effects of tidal energy extraction poses to the coastal environment, using numerical modelling. The numerical evidences yielded in this study show that the amount of energy extraction is largely subjected to bathymetry, the location of the headland, and the flow channel width. Tg Tuan Headland is found as the most promising site for energy extraction with great potential energy production which is able to replace 185 GWh per annum of natural gas in Malaysia. The implementation of 1.5 km Ã 1.5 km intermediary tidal farms headlands in close proximity showed minimal influence to each other, approximately â¼1.3â6.8 reduction in their energy production. The 2D high resolution hydrodynamic modelling results yielded from this study can be served as a good spatial and temporal basis for site selection. Â© 2019 Elsevier Ltd